Ecological eustress? Nutrient supply, bloom stimulation and competition determine dominance of the diatom Didymosphenia geminata. (August 2017) - Bray, Jonathan; Kilroy, Cathy; Gerbeaux, Philippe; Harding, Jon S.
Abstract: Nuisance proliferations of the invasive benthic alga Didymosphenia geminata (Bacillariophyceae) are of major concern in many temperate regions due to their severe effects on river habitats and communities. Proliferations result from the production of basal stalk material, stimulated by phosphorus limited, high light conditions. An unresolved disconnect occurs where nitrogen and phosphorus are observed to stimulate D. geminata cell division, but, within a realised niche, disappearance or establishment failure occurs where dissolved reactive phosphorus (DRP) concentrations occur above c . 2–5 μg/L. Our aims were to examine the mechanisms behind D. geminata bloom stimulation and absence/disappearance. We examined: (1a) whether prolonged nitrogen (NaNO3 – N) and phosphorus (NaH2 PO4 – P) addition would stimulate cell division, and (1b) whether subsequent nutrient limitation stimulated stalk production; (2) whether the mechanism behind D. geminata absence at >5 μg/L DRP, occurred either as (2a) a deleterious consequence of prolonged N + P exposure or (2b) was associated with increasing densities of co‐occurring algae; and (3) whether water velocity stimulated D. geminata cell division thereby influencing outcomes. Didymosphenia geminata cell densities, frequencies of dividing cells, stalk production and densities of competing algae were examined in flow‐through channel mesocosms over 8 weeks. Treatments included: Waitaki River water (control); N + P amended water; and two treatments in which nutrient amendments were changed over time, these being N + P to N, and N + P to Waitaki water. Continued N + P amendment was positively correlated with D. geminata cell densities. N‐replete P‐limited channels, however, accrued greatest densities of D. geminata cells, stalk fragments and dividing cells. Results suggest that within a realised niche short term N + P amendment followed by chronic P limitation could either hasten and/or worsen bloom development. Water velocity influenced community successional trajectories and D. geminata fitness outcomes. Across all nutrient and velocity treatments, a decline in D. geminata cell densities and cell division was correlated with increasing densities of competing algae. Phosphorus limitation stimulating stalk production appears to be an example of physiological stress resulting in increased fitness (known as eustress) and D. geminata dominance. This contrasts with a general pattern of competitive exclusion as nutrient concentrations increase.